Using digitalization tools in training specialists in the field of occupational safety - Tverdokhliebova, Natalia Yevheniivna; Yevtushenko, Nataliia Serhiivna (Видавництво МДПУ ім. Б. Хмельницького, 2025)
The article presents current approaches to training occupational safety specialists in the context of educational digitalization. It highlights the experience of the National Technical University «Kharkiv Polytechnic Institute» in utilizing digital platforms such as Office 365, Moodle, Google Classroom, and Microsoft Teams within the learning process. The advantages of integrating electronic content, video lectures, interactive knowledge assessment tools, and artificial intelligence for learning support and risk management are substantiated. The article emphasizes that the effective use of digital tools enhances the flexibility and individualization of education, contributing to the development of key competencies in future professionals. У статті висвітлено актуальні підходи до підготовки фахівців з охорони праці в умовах цифровізації освіти. Розглянуто досвід Національного технічного університету «Харківський політехнічний інститут» щодо використання цифрових платформ Office 365, Moodle, Google Classroom, Microsoft Teams у навчальному процесі. Обґрунтовано переваги впровадження електронного контенту, відеолекцій, інтерактивних форм перевірки знань, а також використання штучного інтелекту для підтримки навчання та управління ризиками. Підкреслюється, що ефективне застосування цифрових інструментів сприяє гнучкості, індивідуалізації навчального процесу та формуванню ключових компетентностей майбутніх фахівців.
Використання інструментів цифровізації при підготовці фахівців галузі "охорона праці"
Keywords: digitalization; digitalization tools; specialists; occupational safety; educational digitalization; digital platforms; цифровізація; інструменти цифровізації; фахівці; охорона праці; цифровізація освіти; цифрові платформи